Diagnosis of lymphoma in cats: a brief overview of the problem - Bilyi, D.; Suprunenko, O. (Scientific Progress & Innovations, 2025)
Lymphoma is the most common neoplasm in cats. Although hematopoietic tumors account for approximately one-third of all tumors in cats, 90 % of them are lymphomas. Given the controversial nature of many aspects of feline lymphoma verification, an analysis of current diagnostic tests was conducted to further develop an effective step-by-step algorithm for disease detection. Feline lymphoma manifests in various anatomical forms, including alimentary/gastrointestinal, nasal, mediastinal, peripheral nodal, laryngeal/tracheal, renal, central nervous system, cutaneous, and hepatic, with alimentary lymphoma being the most common. The multifaceted nature of the lesions results in a significant diversity of clinical signs, making early detection of the disease difficult. Among the minimally invasive diagnostic methods for lymphoma in cats, ultrasound and X-ray scanning of the chest and abdominal cavities, as well as lymph nodes, are most widely used. Modern visual diagnostics of lymphoma involves the use of computer and magnetic resonance imaging, which are more informative, but currently have limited use (mainly due to the lack of such equipment in veterinary medicine institutions and the high cost of the study). The results of hematological and biochemical tests to a greater extent reflect paraneoplastic syndromes, are characterized by significant fluctuations in indicators. The most important stage in making a final diagnosis is the differential diagnosis of lymphoma lesions, primarily from inflammatory infiltrates. The modern scheme is based on a step-by-step strategy of histomorphological evaluation of biopsy specimens with subsequent immunophenotyping and determination of the clonality of infiltrating T- or B-cells using polymerase chain reaction. This stepwise approach helps to pathomorphologically differentiate neoplastic from inflammatory lymphocytes in biopsy specimens, thereby contributing to the prediction of clinical outcome and the selection of appropriate therapy. The prospect of further research involves improving existing diagnostic schemes for the purpose of early diagnosis of the disease.